2016
DOI: 10.1002/ecs2.1490
|View full text |Cite
|
Sign up to set email alerts
|

Post‐settlement ecological changes in the forests of the Great Lakes National Parks

Abstract: Abstract. National parks of the United States seek to preserve the natural and cultural heritage of the United States, yet parks in the eastern and Midwestern United States were established after periods of human settlement and disturbance. In the Great Lakes region, fire and windfall originally dominated as disturbance agents, driving dynamics in prairies, savannas, and in many forested ecosystems. How ever, fire suppression over the last century has radically lengthened fire return intervals. Additionally, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…Ordination of species composition can reveal human impacts (Paulson et al. ). The management influence (or naturalness) is one possible ordination factor mentioned by several authors (Curtis , Frey , Lõhmus , Cottam et al.…”
Section: Discussionmentioning
confidence: 99%
“…Ordination of species composition can reveal human impacts (Paulson et al. ). The management influence (or naturalness) is one possible ordination factor mentioned by several authors (Curtis , Frey , Lõhmus , Cottam et al.…”
Section: Discussionmentioning
confidence: 99%
“…Paulson et al. (, this issue) documented the shift in forest community composition since the 19th century toward early‐successional species (aspen and maple) and declines in fire‐dependent species (jack pine, red pine, bur oak) and species present during the early 20th‐century cutover (white pine and hemlock). At ISRO, fire was the major disturbance agent between 1843 and 1900 when much of the forest was burned by mining companies to accommodate prospectors (Snyder and Janke ).…”
Section: Discussionmentioning
confidence: 99%
“…The NPS is entrusted with stewarding a rather astounding array of natural resources, that, as reflected here, often span very broad geographic (e.g., Miller et al 2016, Rodhouse et al 2016) and temporal scales (e.g., Ketz et al 2016, Paulsen et al 2016, Roland et al 2016, and multiple levels of ecological complexity (e.g., Coletti et al 2016, Fakhraei et al 2016. The NPS is entrusted with stewarding a rather astounding array of natural resources, that, as reflected here, often span very broad geographic (e.g., Miller et al 2016, Rodhouse et al 2016) and temporal scales (e.g., Ketz et al 2016, Paulsen et al 2016, Roland et al 2016, and multiple levels of ecological complexity (e.g., Coletti et al 2016, Fakhraei et al 2016.…”
Section: Special Feature Highlightsmentioning
confidence: 98%
“…Miller et al (2016) showed that parks in the eastern United States provide significantly older forest structure and different demographic rates than forests outside of parks. Also in the Great Lakes region, Paulsen et al (2016) provide a long view comparing contemporary forest species composition patterns in parks with those recorded during 19th-century public land surveys. Also in the Great Lakes region, Paulsen et al (2016) provide a long view comparing contemporary forest species composition patterns in parks with those recorded during 19th-century public land surveys.…”
Section: Special Feature Highlightsmentioning
confidence: 99%
See 1 more Smart Citation